Comparative eco-efficiency analysis on asphalt pavement rehabilitation alternatives: Hot in-place recycling and milling-and-filling. (10th February 2019) - Cao, Ruijun; Leng, Zhen; Hsu, Shu-Chien
Abstract: With the ever-increasing road mileages worldwide, the focus of pavement construction has been shifted from new pavement construction to pavement maintenance and rehabilitation (M&R). The corresponding huge environmental burdens and capital consumptions posed big challenges in achieving the target of sustainable development. In this study, an eco-efficiency analysis (EEA) framework was developed and applied to compare two common asphalt pavement rehabilitation techniques: hot-in-place recycling (HIRP) and milling-and-filling (M&F), by integrating the life cycle assessment (LCA) and life cycle costing analysis (LCCA), which followed by a sensitivity analysis to investigate the eco-efficiency performances of the two alternatives under different life extension scenarios. The eco-efficiency portfolio positions of hot-in-place recycling and milling-and-filling provided by the eco-efficiency analysis clearly indicated that hot-in-place recycling was more eco-efficient than milling-and-filling under the same assumed service life (15 years) for the cases studied. Hot-in-place recycling could save 5% cost and reduce 16% overall environmental impacts than milling-and-filling, while milling-and-filling saved 7% energy consumption than hot-in-place recycling. When the life extension ratio of the two alternatives reaches 12/15 (HIPR/M&F), milling-and-filling starts to show its advantages in both environmental and economic aspects in the long-term perspective. These findings indicated that if the hot-in-place recycling technique could ensure its treatment effectiveness. Its wider adoption would be championed for more sustainable transportation infrastructure development. The method and results of this study were expected to serve as a reference for decision-makers to make well-informed project decisions on the optimum rehabilitation alternative from the view of eco-efficiency. Highlights: EEA was applied as a new sustainability assessment tool in pavement engineering. An EEA framework was developed for comparing two pavement rehabilitation techniques: HIPR and M&F. With same service life (15 years), HIPR was more eco-efficient, saving 5% cost and reducing 16% overall environmental impacts. With same service life (15 years), M&F saved 7% energy consumption. When the life extension ratio reaches 12/15 (HIPR/M&F), M&F started to show advantages in both environmental and economic aspects.